Technologies Of Disposal Of Industrial Waste With Harmful Chemicals (Eurasian Journal of Engineering and Technology, 2022)
The article deals with the problems of industrial waste disposal. It is noted that the problem of environmental protection is complex and global in nature. Long-term pollution of the natural environment by industrial waste leads to environmental degradation. Due to the numerous industries that supply waste to the external environment, there are some problems with the disposal of this waste. The aggravation of environmental problems against the background of the intensification of production processes requires a revision of approaches to managing processes in the field of waste management.